2019
DOI: 10.1002/lio2.316
|View full text |Cite
|
Sign up to set email alerts
|

A Hidden Epidemic of “Intermediate Risk” Oropharynx Cancer

Abstract: ObjectivesOropharyngeal squamous cell carcinoma (OPSCC) incidence is rapidly increasing in the United States and around the world, driven in large part by infection with the human papillomavirus (HPV). HPV associated OPSCC (HPV+OPSCC) has been shown to have improved response to treatment relative to tobacco‐associated OPSCC. However, improvement in patient survival has not been uniform. Subsets of OPSCC patients in the US and around the world continue to have poor oncologic outcomes. Although the drivers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
(104 reference statements)
0
10
0
1
Order By: Relevance
“…Modern day oncologic outcomes for HPV+ OPSCC are remarkable, considering the relative lack of clinical progress in other HNSCC disease sites 26,27 . Unlike other sites in which survival has remained relatively flat over the last 2-3 decades (oral cavity) or even decreased (larynx), survival for patients with OPSCC continues to improve, driven primarily by a shift in the epidemiology of the disease toward HPV mediated cancers 2 this shift in survival outcomes for patients with OPSCC has been largely uneven across different segments of the US population 12,30 . One prime culprit for this differential response is tobacco exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Modern day oncologic outcomes for HPV+ OPSCC are remarkable, considering the relative lack of clinical progress in other HNSCC disease sites 26,27 . Unlike other sites in which survival has remained relatively flat over the last 2-3 decades (oral cavity) or even decreased (larynx), survival for patients with OPSCC continues to improve, driven primarily by a shift in the epidemiology of the disease toward HPV mediated cancers 2 this shift in survival outcomes for patients with OPSCC has been largely uneven across different segments of the US population 12,30 . One prime culprit for this differential response is tobacco exposure.…”
Section: Discussionmentioning
confidence: 99%
“…HNC affect ∼600,000 patients per year worldwide and is the sixth leading cancer by incidence. Smoking is mainly implicated in the rise of HNC in developing countries, while the human papillomavirus (HPV) is an established important risk factor in the increase of oropharyngeal cancers in developed countries (Ang et al, 2010;Sabatini and Chiocca, 2019;Sandulache et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is also a likely driver of poor outcomes, particularly in the Veteran population with high rates of tobacco use. Smoking worsens prognosis in HPV‐positive OPSCC, increasing the risk of death by 1% for every one pack‐year of smoking 30‐32 . However, to date, few studies have considered the interaction between HIV and HPV in OPSCC, and one previous study of OPSCC among PWLH found no difference in survival by HPV status, 33 This discordance justifies additional examination of the interaction between HPV and HIV in OPSCC specifically.…”
Section: Discussionmentioning
confidence: 99%